2021
DOI: 10.1007/s40974-021-00209-2
|View full text |Cite
|
Sign up to set email alerts
|

Olive mill wastewater effects on durum wheat crop attributes and soil microbial activities: A pilot study in Syria

Abstract: Olive mill wastewater is one of the environmental problems in semiarid regions. The main goals of this study were to investigate the impacts of different olive mill wastewater levels on durum wheat (Triticum aestivum var. Douma1) production and soil microbial activities (i.e., bacteria and fungi). A pot experiment was conducted during the growing seasons 2015/2017 to evaluate the effect of three levels of olive mill wastewater on both growth and productivity attributes of wheat. Vertisol soil samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…On the other hand, our results show a significant effect of OMW on the vegetative growth of tomato plants. These results are comparable to those found by Khalil and al. (2021), where OMW positively affects, at doses of T5 (5 L/m 2 ) and T10 (10 L/m 2 ), the height of wheat plants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, our results show a significant effect of OMW on the vegetative growth of tomato plants. These results are comparable to those found by Khalil and al. (2021), where OMW positively affects, at doses of T5 (5 L/m 2 ) and T10 (10 L/m 2 ), the height of wheat plants.…”
Section: Discussionsupporting
confidence: 92%
“…(2021), where OMW positively affects, at doses of T5 (5 L/m 2 ) and T10 (10 L/m 2 ), the height of wheat plants. This could be attributed to the organic and nutritional loading of OMW, as well as the reduction in levels of phenols and other phytotoxic compounds as a result of the different dilutions [Fausto Cereti and al., 2004;Khalil and al., 2021;Rusan and Malkawi, 2016;Sidari and al., 2010]. This positive vegetative growth is attributed to the high amounts of protein, polysaccharides, humic acids, and macro and micro mineral elements present in these effluents [Faraloni and al., 2023;Sawalha and al., 2014].…”
Section: Discussionmentioning
confidence: 99%
“…The land application of olive mill wastewater has been reported to increase organic matter content and enrich essential inorganic nutrients (P, K, Mg, Fe), vital for promoting plant growth [13]. Numerous studies reported that OMW contributed to positive metabolic and physiological responses in plants, enhancing their growth [4,10,14]. However, interest has arisen regarding its impact not only on subsequent effects on crop productivity but also on soil organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Caruso et al (2018) as well as Chatzistathis and Koutsos (2017) published two valuable studies on the impacts of OMW spreading on soil and crops, their findings revealed that utilizing OMW induced beneficial effects on soil. Moreover, these effluents have been reported to exert adverse effects on plant growth, leading to delays in germination and impeded plant development, primarily attributed to elevated concentrations of phenolic compounds or heavy metals, particularly in non-diluted solutions (Khalil et al, 2021). Despite these documented negative implications, it is crucial to acknowledge that these effluents contain significant nutrient content.…”
Section: Introductionmentioning
confidence: 99%